-15x+11x-3=1-5(x+1)

Simple and best practice solution for -15x+11x-3=1-5(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15x+11x-3=1-5(x+1) equation:


Simplifying
-15x + 11x + -3 = 1 + -5(x + 1)

Reorder the terms:
-3 + -15x + 11x = 1 + -5(x + 1)

Combine like terms: -15x + 11x = -4x
-3 + -4x = 1 + -5(x + 1)

Reorder the terms:
-3 + -4x = 1 + -5(1 + x)
-3 + -4x = 1 + (1 * -5 + x * -5)
-3 + -4x = 1 + (-5 + -5x)

Combine like terms: 1 + -5 = -4
-3 + -4x = -4 + -5x

Solving
-3 + -4x = -4 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-3 + -4x + 5x = -4 + -5x + 5x

Combine like terms: -4x + 5x = 1x
-3 + 1x = -4 + -5x + 5x

Combine like terms: -5x + 5x = 0
-3 + 1x = -4 + 0
-3 + 1x = -4

Add '3' to each side of the equation.
-3 + 3 + 1x = -4 + 3

Combine like terms: -3 + 3 = 0
0 + 1x = -4 + 3
1x = -4 + 3

Combine like terms: -4 + 3 = -1
1x = -1

Divide each side by '1'.
x = -1

Simplifying
x = -1

See similar equations:

| 3(y+6)=2y-2 | | 6=0x | | x+(x+1)=(x+2)-(x-1) | | 3-t/6=7 | | C=81000+18x | | 11a+9a=4a+30 | | 5w^2-2w+3=0 | | x^2+18x+90x=0 | | (7t-3)-(3t+1)=-3(1-3t) | | -2-42=x | | 5.60+.25x=19.85 | | 45x-11=250 | | 2x^2+16x+5= | | x*x+12x+32=0 | | 5(3p-5)+4p=5p-6(p+4) | | 14*30b=-196 | | 176-0.8a=122+a | | 5x+2(3x-4)=80 | | 8x+4y=22 | | -17=v | | 3x+50i=18-5yi | | 45-11x=250 | | y-94=5(x-9) | | -4p-13p-p=-150 | | 4y-14=30 | | 14*30+b=-192 | | y-2=5(x+3)fory | | y-9=5(x+8) | | 175+15d=250 | | 61n=187 | | 81-16t^2= | | 33=9-y |

Equations solver categories